2020
DOI: 10.3390/su12125140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Verbal Behavior Training on Performance for Sustainable Development in Childhood and Early Adolescence

Abstract: The effective teaching of language is an aspect of special relevance regarding the good adjustment of children in contexts such as school, family, or community. This article performs an experimental procedure to check which language teaching methodology is most effective in a sample of children. The objective was to analyze the influence of training, Condition 1 (pure tacts more intraverbal) or Condition 2 (pure tacts more impure tacts), on emergence of two tests involving impure tacts (AB-C, AB-D) and four ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(118 reference statements)
1
5
0
Order By: Relevance
“…Participants achieved greater success on the posttests in comparison with the previous experiment. Taken together, these findings seem to indicate that having a history of learning with compound stimuli (Phase 8) allows, to a greater extent, the transfer of what has been learned to new posttests (10, 11, 12) that include these types of stimuli, an aspect that is consistent with the data reported by Maldonado et al (2020).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Participants achieved greater success on the posttests in comparison with the previous experiment. Taken together, these findings seem to indicate that having a history of learning with compound stimuli (Phase 8) allows, to a greater extent, the transfer of what has been learned to new posttests (10, 11, 12) that include these types of stimuli, an aspect that is consistent with the data reported by Maldonado et al (2020).…”
Section: Resultssupporting
confidence: 90%
“…Through the data found, it can be confirmed that the discrimination of the participants is produced through the structure of one to many, appearing this discrimination in tests with compound stimuli, after training with simple stimuli. Until now, research related to compound stimuli has shown better performance when participants have had a learning history with these compound stimuli (see Alonso‐Álvarez, 2010; Alonso‐Álvarez & Pérez‐González, 2006; Alós et al, 2013; Guerrero et al, 2015; Maldonado et al, 2020; Pérez‐González & Alonso‐Álvarez, 2008). If the results found here are confirmed, the mere teaching of simple stimuli (the present experiment) or paired stimuli (Carnerero & Pérez‐González, 2015; Carnerero et al, 2019) could allow for learning to transfer to new operants with simple or compound stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2016) and Jennings and Miguel (2017) used tact and intraverbal training to establish equivalence classes. Additionally, three experiments compared intraverbal training to tact training (6.1%; Daly & Dounavi, 2020; Maldonado et al., 2020; Wu et al., 2019). Nearly one third of experiments (29.2%) investigated the intraverbal as the dependent variable.…”
Section: Resultsmentioning
confidence: 99%